ANALISIS KEBUTUHAN PROJECT BOOK BERBASIS PJBL-STEAM PADA MATA KULIAH METODE EKSPERIMEN FISIKA - Rasmi, Dian Pertiwi; Hendri, Menza; Nasution, Okta Senira Mamora (EduFisika: Jurnal Pendidikan Fisika, 2022)
The importance of experimental science for both researchers and students causes the physics experimental method course to be evaluated and developed, one of which is by analyzing fundamental problems and appropriate solutions in the form of finding appropriate teaching material needs to be developed. The type of research used is qualitative research with research subjects, namely students from the class of 2020. And the data collection technique is by conducting unstructured interviews with item questions, namely open questions. Data analysis was carried out descriptively so that the data would be arranged in a specific pattern and narratively draw conclusions. It was found that the fundamental problem of the course was the absence of learning guidelines so that learning took place unsystematically so that a teaching material could combine STEAM and PjBL. This research will be followed up with further research regarding the development of the STEAM-PJBL-based Project Book, which is expected to be able to answer all the problems contained in the course.